African Americans’ Empowerment through Leadership in The Autobiography of Miss Jane Pittman by Ernest Gaines - AZON, Sènakpon Adelphe Fortuné; KOUGNANVO, Armand; KPOHOUE, FERDINAND (My University, 2017)
Lots of biases still encage black people in the US in the role of content subservient beings for whom the battles for liberation from slavery and full equality have always been waged from without, or only with the support and encouragement of white benevolent do-gooders. The duty to tell the local stories of the struggles for liberation waged by black people themselves through individual commitment and battles, and small-scale leadership is therefore a necessity. Within the interpretive frameworks of new historicism and cultural studies, this paper probes the local, small narratives of African Americans in their fight for freedom, for an egalitarian society, and their resistance to white supremacy and dehumanizing cruelties. It focuses on Ernest J. Gaines’s The Autobiography of Miss Jane Pittman and analyzes the evolution of black “local” leadership from the Emancipation Proclamation to the 1960s Civil Rights movement as it appears in the novel. Beaucoup de préjugés encagent encore les Noirs, aux États-Unis, dans le rôle d'êtres asservis et soumis pour qui les batailles pour la libération de l'esclavage et pour l’égalité intégrale ont toujours été menées de l'extérieur, ou seulement avec le soutien et l'encouragement des bienveillants bienfaiteurs blancs. Le devoir de raconter les histoires locales des luttes de libération menées par les Noirs eux-mêmes à travers l'engagement individuel et les batailles, et le leadership local est donc une nécessité. A travers les approches critiques d’analyse du néo historicisme et du cultural studies, le présent article explore les petits récits locaux des Afro-Américains dans leur combat pour la liberté et pour une société égalitaire, et leur résistance à la suprématie blanche et à la cruauté déshumanisante. L’étude est menée dans le roman L'Autobiographie de Miss Jane Pittman d'Ernest J. Gaines et met l’accent sur l'évolution du leadership «local» noir, entre les deux genres, depuis la proclamation de l'émancipation jusqu’au mouvement des droits civiques des années 1960, tel que cela apparaît dans le roman.
Keywords: African American – leadership – freedom – fight – equality - Afro-américain - leadership - liberté - lutte - égalité